1998
DOI: 10.1002/(sici)1099-0739(199810/11)12:10/11<725::aid-aoc777>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Boron-modified polysilylcarbodi-imides as precursors for Si-B-C-N ceramics: Synthesis, plastic-forming and high-temperature behavior

Abstract: The synthesis, by two different reaction pathways, of boron-modified polysilylcarbodi-imides of general type {B[C 2 H 4 Si(R)NCN] 3 } n (R = singly bonded organic ligand) and the plasticforming and the thermal behavior of these polymers are described. Compounds {B[C 2 H 4 Si(R)NCN] 3 } n [2a, R = H; 2b, R = CH 3 ; 2c, R = (NCN) 0.5 ] can be obtained by treatment of the vinyl-substituted polysilylcarbodi-imides [(H 2 C=CH)(R)SiNCN] n [1a, R = H; 1b, R = CH 3 ; 1c, R = (NCN) 0.5 ] with borane dimethylsulfide BH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…1, indicates the formation of various covalent bonds. Asymmetric stretching bands of the N-H and Si-H units are observed at 3393 cm À1 , 1176 cm À1 , and 2156 cm À1 , respectively [17]. A strong and broad vibration band overlapping with C-H group appears at 1403-1408 cm À1 and at 1380 cm À1 .…”
Section: The Bond Formation Of Preceramic Polymermentioning
confidence: 91%
“…1, indicates the formation of various covalent bonds. Asymmetric stretching bands of the N-H and Si-H units are observed at 3393 cm À1 , 1176 cm À1 , and 2156 cm À1 , respectively [17]. A strong and broad vibration band overlapping with C-H group appears at 1403-1408 cm À1 and at 1380 cm À1 .…”
Section: The Bond Formation Of Preceramic Polymermentioning
confidence: 91%
“…[61][62][63][64][65][66][67] Another route for the synthesis of Si-B-C-N ceramics is by means of thermolysis of borazine-based oligosilazanes 2,6,[68][69][70][71][72][73] or boron-modified polysilylcarbodiimides. [74][75][76] Thus, a great variety of preceramic organosilicon polymers have been developed that could be used to produce ceramic materials with a wide range of compositions in the system Si-B-C-N-O and additional metallic constituents, such as Ti, Al and Zr. 77,78 In order to understand the materials properties of PDCs at a fundamental level, several modelling and computational studies have been reported, [79][80][81][82][83][84][85] not at least to derive a meaningful and understandable interpretation of the experimental data.…”
mentioning
confidence: 99%
“…Polyborosilylcarbodiimides are another important class of precursors for SiBCN ceramics. These polymers can be successfully synthesized by the reaction of tris chlorosilyl-ethyleneboranes BC 2 H 4 SiRCl 2 3 with an excess of bistrimethylsilylcarbodiimide Scheme 9: 74,75,166 Unfortunately, the ceramics obtained from these polymers do not possess satisfactory ultra high-temperature properties, since the thermal degradation already starts at Tࢽ1500c C. Preliminary studies suggested that the degradation temperature strongly depends on the nitrogen content of the samples. 163 In order to reduce the amount of nitrogen, a dehydrocoupling reaction of trishydridosilyl-ethyleneboranes with cyanamide, H 2 N-CN was developed.…”
mentioning
confidence: 99%
“…Here the warm pressing is used as the means of shaping the pre-ceramic polymers by heating them to the temperature where particles of the polymer can be deformed by viscous flow, or above their melting point, and pressing them into a die of desired geometry. [1][2][3][4][5][6] After cooling down to ambient temperature a polymer "green body" is obtained. The method has been successfully applied for shaping of precursors of aluminium nitride, 1 silicon carbonitrides, [4][5][6] and silicon boron carbonitrides.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been successfully applied for shaping of precursors of aluminium nitride, 1 silicon carbonitrides, [4][5][6] and silicon boron carbonitrides. 2,3,6 In most cases the warm pressed green bodies have much higher density than the bodies prepared by, e.g., cold isostatic pressing (CIP) of polymer powders. This is explained by plastic deformation of polymer particles so that the porosity in green body is partially eliminated by mutual sliding of polymer particles and by viscous flow.…”
Section: Introductionmentioning
confidence: 99%